Pengaruh Efikasi Diri dan Manajemen Waktu Terhadap Self-Regulated Learning Pada Siswa SMA Ahmad Yani Binjai - Dachi, Elisabeth Arsenda; Wardani, Retno; Sumampow, Abigail Trifosa; Tarigan, Beby Astri; Marpaung, Winida; Safarina, Nur Afni (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
The research method used was quantitative. Data were collected from 177 student respondents using three instruments, namely the Self-Regulated Learning scale consisting of 25 items, the Self-Efficacy scale consisting of 31 items, and the Time Management scale consisting of 27 items. The results of the major hypothesis test showed that Self-Efficacy and Time Management significantly influenced Self-Regulated Learning, with F = 85.259 and sig = 0.000 (p < 0.05). The results of the minor hypothesis test indicated a positive relationship between Self-Efficacy and Self-Regulated Learning with sig = 0.022 (p < 0.05) and β = 0.204, as well as a positive relationship between Time Management and Self-Regulated Learning with sig = 0.000 (p < 0.05) and β = 0.530. Overall, Self-Efficacy and Time Management contributed effectively by 48.9% to Self-Regulated Learning. Elements not included in the analysis accounted for 51.1%.